Study on Power Grid Partition Method for Wide-area Relaying Protection - Li, Zhenxing; Yin, Xianggen; Zhang, Zhe; Wang, Yuxue (Elektronika ir Elektrotechnika, 2013)
Recently, wide area relaying protection (WARP) is attracting wide concern for its advantages in coping with challenges to traditional backup protection. It is essential for power grid partition based on limitation of WARP having real-time and rapidity. As a result, a novel concept, limited wide area relaying protection system, is proposed and some basic partition principles, including main substation selection, regional scope and multi-regional overlap, are elaborated for helping to realize WARP in whole power grid. Furthermore, the implementation methods of grid partition is proposed by using matrix calculation on grid topological structure of graph theory, and the process is given based on IEEE 11 nodes system partition. A simulation of 220 kV grid systems in Easter Hubei province shows the effectiveness of grid partition for wide-area relaying protection. DOI: http://dx.doi.org/10.5755/j01.eee.19.3.1259